Could schizotypy protect against the negative outcomes of borderline traits on alcohol consumption? A cluster analytic study. (November 2018) - Bronchain, Jonathan; Chabrol, Henri; Raynal, Patrick
Highlights: No study focused on co-occurring schizotypal and borderline traits and alcohol use. Borderline traits may influence alcohol use. Schizotypal traits could protect from alcohol consumption. Schizotypal traits would be protective against the negative impact of borderline traits on alcohol consumption. Abstract: Schizotypal and borderline personality traits seem to be differently associated to alcohol use in young adult. However, no study has explored co-occurring schizotypal and borderline traits in their link with alcohol consumption. Participants were 1572 students from different French universities who completed self-report questionnaires assessing these three dimensions. A cluster analysis based on the borderline and schizotypal traits scores yielded four distinct groups characterized by low schizotypal and borderline traits (LT), high borderline traits (HB), high schizotypal and borderline traits (HT) and high schizotypal traits (HS). The HS cluster had significantly lower alcohol use than the other three groups. LT and HT clusters did not differ significantly in their alcohol use. Comparison between clusters suggests that schizotypal traits may be protective against the negative impact of borderline traits on alcohol consumption. In the context of a co-occurrence between borderline and schizotypal traits, this study provides important information about their link with alcohol consumption.